PRO KONTRA KEBIJAKAN PEMBATASAN BARANG BAWAAN LUAR NEGERI: OPTIMALISASI PERAN BEA CUKAI VIS A VIS MISPERSEPSI PUBLIK - Prayitno, Arief (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2024)
This study highlights the vital role of Customs in overseeing freight forwarding companies (FFCs) and efforts to enhance compliance with customs regulations. Customs is responsible for safeguarding national security, protecting domestic industries, and ensuring fair market competition. However, complex challenges arise, particularly regarding FFCs' compliance with regulations. Many FFCs face difficulties in managing customs documents due to lack of knowledge and adequate systems, often resulting in goods seizures and consumer dissatisfaction. To address these issues, the study recommends several strategic steps. Firstly, Customs should implement comprehensive and regular audits of FFCs, including document checks, physical inspections of goods, and internal procedure evaluations. Audits help identify non-compliance and provide improvement recommendations. Secondly, leveraging information and communication technology (ICT) such as online platforms for document reporting and verification can enhance efficiency and transparency. The use of big data technology and predictive analytics can also assist in risk assessment. Effective communication with the public is crucial to increase understanding of procedures and reasons behind goods seizures. Through public education and responsive customer service, Customs can mitigate public dissatisfaction. Collaboration with other relevant agencies such as the Ministry of Trade and Quarantine Agency is also necessary to expedite document verification processes. Training and capacity building for Customs staff must also be enhanced. In conclusion, by implementing these strategic measures, Customs is expected to improve performance and public trust in both Customs and FFCs, creating a fair and secure trading environment that supports economic growth and societal welfare.